2020
DOI: 10.7554/elife.58073
|View full text |Cite
|
Sign up to set email alerts
|

Atg1 kinase in fission yeast is activated by Atg11-mediated dimerization and cis-autophosphorylation

Abstract: Autophagy is a proteolytic pathway conserved from yeasts to mammals. Atg1 kinase is essential for autophagy but how its activity is controlled remains insufficiently understood. Here, we show that, in the fission yeast Schizosaccharomyces pombe, Atg1 kinase activity requires Atg11, the ortholog of mammalian FIP200/RB1CC1, but does not require Atg13, Atg17, or Atg101. Remarkably, a 62-amino-acid region of Atg11 is sufficient for the autophagy function of Atg11 and for supporting the Atg1 kinase activity. This r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 59 publications
2
25
0
Order By: Relevance
“…Atg11 and Atg17 were also observed to self-interact in the Pil1 co-tethering assay (Fig. S1E,F, 4B,C,D,E), consistent with previously published results showing that both Atg11 and Atg17 can homodimerize (Nanji et al, 2017;Pan et al, 2020). Together, within the fission yeast Atg1 complex, the Pil1 co-tethering assay recapitulated six previously known binary interactions (Atg1-Atg11, Atg13-Atg17, Atg13-Atg101, Atg1-Atg13, Atg11-Atg11, and Atg17-Atg17), and identified two previously unknown binary interactions (Atg1-Atg17 and Atg11-Atg13).…”
Section: Pil1 Co-tethering Assaysupporting
confidence: 92%
See 3 more Smart Citations
“…Atg11 and Atg17 were also observed to self-interact in the Pil1 co-tethering assay (Fig. S1E,F, 4B,C,D,E), consistent with previously published results showing that both Atg11 and Atg17 can homodimerize (Nanji et al, 2017;Pan et al, 2020). Together, within the fission yeast Atg1 complex, the Pil1 co-tethering assay recapitulated six previously known binary interactions (Atg1-Atg11, Atg13-Atg17, Atg13-Atg101, Atg1-Atg13, Atg11-Atg11, and Atg17-Atg17), and identified two previously unknown binary interactions (Atg1-Atg17 and Atg11-Atg13).…”
Section: Pil1 Co-tethering Assaysupporting
confidence: 92%
“…S1C,D, S2A,B, 4D,E). These four pairs of interactions are consistent with previously published results obtained using in-vitro pull-down of recombinant proteins (Nanji et al, 2017;Pan et al, 2020), indicating that these pairs of relatively strong interactions identified by the Pil1 co-tethering assay are direct physical interactions.…”
Section: Pil1 Co-tethering Assaysupporting
confidence: 91%
See 2 more Smart Citations
“…Previously we showed that ZZ2 and ZZ3 together are sufficient for binding Lap2 and Ape2 (Liu et al, 2015). To systematically map the cargo-interacting regions of Nbr1, we employed an imaging-based method, termed Pil1 co-tethering assay, to examine pairwise protein-protein interactions (Pan et al, 2020). In this assay, we fuse a bait protein to Pil1, which forms filamentary structures.…”
Section: Resultsmentioning
confidence: 99%